ANÁLISE DA SUFICIÊNCIA DA ATIVIDADE FÍSICA ASSOCIADO AO ÍNDICE DE DESENVOLVIMENTO HUMANO MUNICIPAL NAS CAPITAIS BRASILEIRAS - Dartel Ferrari Lima; Olinda do Carmo Luiz (Universidade Estadual do Oeste do Paraná, 2013)
The Municipal Human Development Index (MHDI) is proposed to measure the development stage of a population in a certain space and time. Determinants whit income, education and health compose the facets used in the calculation of this index. The practice of physical activity (PA) in everyday life presents itself as an important indicator of health. This article is concerned with knowing the correlation between the prevalence of PA enough with their respective domicile's MHDI. The correlated data were collected through the report of the Surveillance System of Risk Factors for Chronic Diseases Protection Telephone Survey (VIGITEL/2010) and the Firjan Municipal Development Index (MHDI)/2009. All capitals of the Federation showed a FMDI moderate to high, with a higher value for the city of Curitiba (0.87) and lower for the city of Rio Branco (0.69). The two more prevalence of individuals sufficiently active (22.4% and 20%) were found in Brasilia and Palmas, occupying the 8th and 17th position in the ranking of MHDI, respectively. The capitals of the northern region of the country had lower MHDI and accumulated the highest prevalence of PA enough. This study did not find statistically significant correlation between individuals considered sufficiently active and MHDI in the capitals of the Federation (r = 0.14).